The Influence of Organizational Climate, Organizational Culture, Leadership, and Position Promotion on Employee Performance at the Office of Cooperatives and SMEs in Labuhanbatu Regency - Nurjanah Nurjanah; Elvina Elvina; Abdul Halim (Quantitative Economics and Management Studies, 2023)
This research was conducted at the Office of Cooperatives and SMEs in Labuhanbatu Regency, with the aim of knowing the effect of Organizational Climate, Organizational Culture, Leadership and Position Promotion on Employee Performance. This study uses quantitative methods, with several analytical techniques such as the classical assumption test, multiple linear regression test, hypothesis testing and coefficient of determination test. All hypotheses in the research are stated to be valid, it can be proven by the following description, organizational climate variable (2,520) > ttable (1.691) which means that Ha is accepted and Ho is rejected. While the significant value is smaller than the probability value of 0.017 or a significant value of 0.000 <0.017. Thus it can be concluded that the Organizational Climate variable (X1) has a positive and significant effect on Employee Performance. Organizational Culture (X2) has a tcount (3.145) > ttable (1.691) which means that Ha is accepted and Ho is rejected. While the significant value is smaller than the probability of 0.004 or a significant value of 0.000 <0.004. Thus it can be concluded that Organizational Culture (X2) has a positive and significant effect on Employee Performance. Leadership (X3) has a tcount (2.857) < ttable (1.691) which means that Ha is rejected and Ho is accepted, while the significant value is smaller than the probability of 0.05 or 0.000 <0.007. Thus it can be concluded that Leadership (X3) has a positive and significant effect on Employee Performance. Promotion (X4) has a tcount (2.457) > ttable (1.691) while the significant value is smaller than the probability of 0.05 or 0.000 <0.019. Thus it can be concluded that Promotion (X4) has a positive and significant effect on Employee Performance. The results of the F test show that the Fcount value is 11,521 > Ftable 2.503 with a significance value of 0.000 <0.05. From these results, it can be concluded that Organizational Climate (X1), Organizational Culture (X2) Leadership (X3), and Promotion (X4) simultaneously have a positive and significant effect on Employee Performance (Y). Furthermore, an analysis of the coefficient of determination was carried out to analyze the contribution of the influence of the independent variables, namely organizational climate.